Akuntansi Ilabulo: Studi Etnometodologi Islam - Thalib, Mohamad Anwar; Polapa, Asma; Rumampuk, Rismawati; Ma’luna, Sri Salni Safitri (Penerbit Goodwood, 2023)
Purpose: Purpose: This study aims to construct labulo accounting practices based on local cultural values. Methodology/Approach: This study employs the Islamic framework from an Islamic ethno-methodology perspective. It uses a qualitative methodology that incorporates two data-gathering methods: structured interviews and passive participant observation. The participants in this study were chosen using purposive sampling techniques. The data analysis process consisted of five phases: amal, ilmu, iman, informasi wahyu, and ihsan. Results/Findings: The results indicate three ways in which Ilabulo traders practice accounting: profit accounting, loss accounting, and simple memory-based recording. These accounting practices are characterized by trustworthiness (amanah) and patience (kesabaran). Trustworthiness is reflected through sellers' actions, using their trading profits to support their families’ needs and children's education. The elders often advise the value of family responsibility through the expression (lumadu)